PENGARUH KINERJA KARBON, TEKANAN STAKEHOLDER DAN SERTIFIKASI ISO 14001 TERHADAP PENGUNGKAPAN EMISI KARBON - Hanisyah Iratiwi; Sulfitri, Virna (Postgraduate Management Journal, 2023)
This study was conducted to obtain empirical evidence that carbon performance, stakeholder pressure and ISO 14001 certification affect the disclosure of company carbon emissions. In this study, the size of the company, leverage, profitability and capital expenditure as control variables. This study uses quantitative methods as a research approach. All non-financial companies listed on the Indonesia Stock Exchange (IDX) are the population in this study and data in the form of annual report data and sustainability reports of non-financial companies. In this study, the determination of the sample was carried out by purposive sampling method. Based on the data that has been collected and the tests that have been carried out on 72 samples of companies using the panel data regression model, it can be concluded that carbon performance, company size and leverage have no significant effect on carbon emission disclosures, stakeholder pressure and capital expenditure have a significant positive effect on emission disclosures. carbon, ISO 14001 certification does not support a positive but significant negative effect and profitability has a significant negative effect on the disclosure of carbon emissions of non-financial companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period.